2017
DOI: 10.1136/lupus-2017-000213
|View full text |Cite
|
Sign up to set email alerts
|

Early proteinuria response: a valid real-life situation predictor of long-term lupus renal outcome in an ethnically diverse group with severe biopsy-proven nephritis?

Abstract: ObjectiveTwo recent important lupus nephritis trials reported that proteinuria was a good predictor of renal outcome in Caucasians, but data on real-life situation, other races and severe nephritis are lacking to substantiate this finding as a simple test to guide clinical practice. The aim of this study was to validate proteinuria as a predictor of long-term renal outcome in real-life situation in a racially diverse group of patients with severe nephritis.MethodsProteinuria, serum creatinine (SCr) and urine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 24 publications
8
69
0
2
Order By: Relevance
“…Additionally, a proteinuria level of 0.7-0.8 gm/day after 12 months of treatment was recently identified as the best predictor of long-term kidney survival compared to serum creatinine and urinary RBC status in a post hoc analysis of the Euro-Lupus Nephritis Trial and MAINTAIN LN trials (18,19). These results were verified in an independent, ethnically diverse LN cohort (20). Similarly, proteinuria is a key component of all of our risk models, whereas urinary RBCs are not.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, a proteinuria level of 0.7-0.8 gm/day after 12 months of treatment was recently identified as the best predictor of long-term kidney survival compared to serum creatinine and urinary RBC status in a post hoc analysis of the Euro-Lupus Nephritis Trial and MAINTAIN LN trials (18,19). These results were verified in an independent, ethnically diverse LN cohort (20). Similarly, proteinuria is a key component of all of our risk models, whereas urinary RBCs are not.…”
Section: Discussionmentioning
confidence: 71%
“…Post hoc analyses from the MAINTAIN and Euro-Lupus Nephritis Trials suggest that proteinuria at 12 months represents the best single predictor for long-term renal outcome (ie, risk for end-stage kidney disease (ESKD) or doubling of serum creatine after 10 years). [23][24][25][26][27] Accordingly, therapy should aim for proteinuria <0.5-0.7 g/24 hours by 12 months (complete clinical response), although up to 50% of patients not reaching this milestone may still have stable longterm kidney function. 25 28 Evidence of improvement in proteinuria (with GFR normalisation/stabilisation) should be noted by 3 months, 29 30 and at least 50% reduction in proteinuria (partial clinical response) by 6 months.…”
Section: Treatment Of Adult Ln Goals Of Treatmentmentioning
confidence: 99%
“…By contrast, early decrease of proteinuria levels over 6 months of treatment has shown ability to predict a more favourable long-term renal outcome compared with patients with persistently high-grade proteinuria,16 and a recent series of three studies of similar design concluded that the most useful clinical predictor of good long-term renal outcome (defined using a cut-off for serum concentrations of creatinine at 7 years after the LN episode) is proteinuria levels <0.7–0.8 g/day at month 12 from treatment initiation 14 15 17. Nevertheless, while this clinical target could identify patients who had a good renal outcome with a high positive predictive value, it could not predict the outcome of patients who did not achieve the target since the negative predictive value of this proteinuria cut-off was low in two of the three investigations 14 15.…”
Section: Clinical Predictorsmentioning
confidence: 99%